Do Human Resource Management Practices Improve Employee Performance? The Mediation Role of Job Satisfaction in Indonesian MSMEs - Indrayani, Tri Irfa; Fermayani, Riche; Egim, Ash Shadiq; Chen, Liping; Andra, Yefrinal (Universitas Muhammadiyah Yogyakarta, 2025)
Research aims: This study aims to investigate the influence of Human Resource Management (HRM) practices on employee performance, with job satisfaction serving as a mediating variable, within the context of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia.Design/Methodology/Approach: Data were collected using structured questionnaires distributed to owners and employees of MSMEs in Indonesia. The sampling technique used was purposive sampling, resulting in a total of 130 valid responses. Data analysis was conducted using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software.Research findings: The results of the study indicate that HRM practices have a positive and significant effect on employee performance. Furthermore, job satisfaction significantly mediates the relationship between HRM practices and employee performance. These findings suggest that enhancing HRM practices can increase employee job satisfaction, which in turn leads to improved performance.Theoretical Contribution/Originality: The findings of this study can serve as a valuable reference for policymakers in designing programs and policies that support the enhancement of HRM practices within the MSME sector. Strengthening HRM practices can contribute to increased employee satisfaction and performance, which in turn promotes the overall growth and competitiveness of MSMEs in Indonesia.Practitioners/Policy Implications: The practical implication of this study highlights the importance for MSME managers to implement effective HR strategies aimed at enhancing employee job satisfaction. By prioritizing well-structured HR practices, MSME managers can foster a more motivated and productive workforce, thereby improving overall organizational outcomes.Research Limitations/Implications: This study focuses primarily on HRM practices and job satisfaction as the main variables influencing employee performance. However, it acknowledges that employee performance is also affected by other important factors, which were not examined in this research. Future studies are encouraged to explore these additional variables to provide a more comprehensive understanding of the determinants of employee performance within the MSME sector.